2020
DOI: 10.3390/jcm9061916
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Pathophysiology Underlying Constipation in Parkinson’s Disease: Implications for Cognitive Inefficiency

Abstract: Depression is associated with constipation within and outside Parkinson’s disease (PD). Since inefficient cognitive-processing (bradyphrenia) features in PD and an enterokinetic agent improved cognitive performance in healthy individuals, bradyphrenia may be associated with constipation. We aim to define the archetypical bowel function of PD, and its association with cognition, mood, and motor features within and outside PD. We assessed colonic transit time (oral radio-opaque markers over 6 days), bowel functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Because PD patients often have a degree of gut inflammation, faecal calprotectin is frequently raised ( Weis et al, 2019 ) and has been suggested as an early biomarker for PD risk ( Mulak et al, 2019 ). The GI abnormalities (particularly permeability issues and the finding of intestinal inflammation) found in PD are common to many other diseases, but their importance is that these changes may reflect pathophysiological processes that aggravate certain symptoms of PD ( Tucker et al, 2020a , Tucker et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…Because PD patients often have a degree of gut inflammation, faecal calprotectin is frequently raised ( Weis et al, 2019 ) and has been suggested as an early biomarker for PD risk ( Mulak et al, 2019 ). The GI abnormalities (particularly permeability issues and the finding of intestinal inflammation) found in PD are common to many other diseases, but their importance is that these changes may reflect pathophysiological processes that aggravate certain symptoms of PD ( Tucker et al, 2020a , Tucker et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…Overgrowth in PD is likely to result from reflux of microbiota from a stagnant ascending colon. 1 Indeed, the higher prevalence of hydrogen breath test positivity with a lactulose substrate than when using the absorbable sugar, glucose, may represent distal colonisation. 13 …”
Section: Discussionmentioning
confidence: 99%
“…Bowel function was defined by (i) questionnaires: Rome III functional constipation for its presence/absence, 33 and Bristol Stool Scale for consistency of stool (1–7), 34 (ii) colonic transit time using pellets containing radio‐opaque barium markers (Transit‐Pellets, Medifactia, Stockholm, Sweden), swallowed on 6 consecutive days. 1 An abdominal radiograph was taken on day 7, approximately 12 h after the last pellet. All radiographs were assessed (blind to participant identity/group) by the same specialist gastroenterological radiologist.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anxiety is one of pre-diagnostic features of PD, predated by another NMS (27). Anxiety is higher in PD patients compared to controls in a large sample of early diagnosed PD subjects (28).…”
Section: Anxietymentioning
confidence: 99%